H-ras aktif fibroblast hücre apoptozunun bazı 1,3-bis-(heteroaril substitue) benzen türevleri ile uyarılması,[Apoptosis of h-ras fibroblast cells is stimulated by some 1,3-bis-(heteroaryl substituted) benzene derivatives] - Gulsen Akalın (De Gruyter, 2006)
Apoptosis is a normal physiological process which occurs during embryonic development and the maintenance of tissue homeostasis. Nowadays, it is known that some chemotherapeutic agents are able to activate the pathway of apoptosis in cells. Therfore, it is valuable to investigate the cytotoxic and apoptotic effects of some 1,3-bis- (heteroaryl substituted) benzene derivatives (MBİS1, MBİS2 and MBİS8) that might be potential anti-tumour drugs, on rat embryo fibroblast F2408 (normal cell line) and 5RP7 (H-ras transformed cell line). The results showed that the selective and significant cytotoxic effects were observed by treatment of 5RP7 cells with either MBİS1 or MBİS8 for 24 hours. Correspondingly, incubation with 0,001 and 0,002 mg/ml MBİS1 or 0,0006 mg/ml MBİS8 lead to the appeaance ofr morphological apoptotic changes. However the mechanism of early apoptosis on both F2408 and 5RP7 cell lines was not triggered in the presence of both derivatives compared to positive control (Etoposid 25 µM). On the other hand, the DNA fragmentation on genomic DNA of 5RP7 cells was observed with only MBİS8 (0,005 mg/ml) treatment for 9 or 24 hours. This observations indicated that these two benzene derivatives might be usefulin in chemotherapy therefore it may be useful to carry out further investigations on these agents.